2017
DOI: 10.4314/ahs.v17i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of faith-based organisations on HIV prevention strategies in Africa: a systematic review

Abstract: BackgroundThe HIV/AIDS epidemic remains of global significance and there is a need to target sub-Saharan Africa since it is the hardest hit region worldwide. Religion and more specifically faith-based organisations can have an effect on socio-cultural factors that increase or decrease the risk of infection; and offer preventative interventions to the wider community.ObjectiveTo understand the influence of faith-based organisations on HIV prevention in Africa.MethodThe main search engine of a British university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…HIV prevention was not identi ed as a separate theme in this research priority setting, despite being described in the literature as an important focus for future faith involvement. 26 Some respondents consider faith involvement in HIV prevention as controversial and feel that it should therefore not be a current focus of research. Even in countries such as Brazil, where faith-based organisations are highly integrated into service delivery for people living with HIV, prevention services are generally not carried out by these organisations.…”
Section: Discussionmentioning
confidence: 99%
“…HIV prevention was not identi ed as a separate theme in this research priority setting, despite being described in the literature as an important focus for future faith involvement. 26 Some respondents consider faith involvement in HIV prevention as controversial and feel that it should therefore not be a current focus of research. Even in countries such as Brazil, where faith-based organisations are highly integrated into service delivery for people living with HIV, prevention services are generally not carried out by these organisations.…”
Section: Discussionmentioning
confidence: 99%
“…The central role of religion in the lives of many Africans also means that the ways that RLs discuss issues such as HIV/AIDS, risk behavior, and sexuality can have important effects on their congregants' beliefs and attitudes toward HIV prevention. 6,9…”
Section: Discussionmentioning
confidence: 99%
“…Church involvement in the response to the HIV epidemic in southern Africa has tended to be on prevention messaging, counseling, and support and care for those infected and affected by the disease. 6,7 There is little evidence of individual churches or congregations directly participating in implementing HTS. Some evidence exists of the potential role of churches in encouraging member to test for HIV; Eriksson et al 8 found that youth in faith communities that receive higher levels of education on HIV prevention are more likely to test for HIV.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Next we have a paper on adherence to ART, 15 decentralization of ART management, 16 and influence of faith based organizations on HIV prevention. 17 One paper documents HBV DNA gene polymorphisms prediction of chronic HBV infection in India. 18 …”
Section: Infectious Diseasesmentioning
confidence: 99%